A fluorescent probe for sensing ferric ions in bean sprouts based on l-histidine-stabilized gold nanoclusters. Issue 2 (5th December 2014) - Su, Yuan; Qi, Li; Mu, Xiaoyu; Wang, Minglin
Abstract : Fluorescentl -histidine-stabilized Au NCs were successfully synthesized by a green one-pot process sincel -histidine played dual roles as both a stabilizer and a reducing agent. Moreover, the prepared Au NCs were used as a novel fluorescent probe for selective sensing of ferric ions in bean sprouts. Abstract : In this work, l -histidine-stabilized gold nanoclusters were prepared by a green one-pot process and employed as a selective probe for sensing ferric ions. The obtained probe exhibited bluish green fluorescence, and exhibited an excitation maximum at 394 nm and emission maximum at 492 nm. The fluorescence of the probe was obviously quenched by the introduction of ferric ions, hinting that the synthesized probe could be applied for sensing ferric ions. Further, the selectivity of the proposed probe for sensing ferric ions was investigated. The results indicated that the fluorescent probe had favorable sensitivity and selectivity for the detection of ferric ions. Moreover, this probe was further used for the analysis of ferric ions in bean sprouts. It showed that the gold nanocluster based fluorescent probe has great potential for sensing metal ions in plants.